The role of neutrophils in the pathogenesis of atherosclerosis - Yu. V. Saranchina; S. V. Dutova; O. Yu. Kilina; N. V. Khanarin; T. S. Kulakova (Кардиоваскулярная терапия и профилактика)
Atherosclerosis (AS) is one of the causes of cardiovascular disease. The formation of atherosclerotic lesions of the arteries is a long process, and clinical symptoms appear already at the stage of atherosclerotic plaque (ASB), which prevents blood flow and can cause coronary heart disease, as well as acute coronary syndrome. The study of atherosclerosis mechanisms at the subclinical level is relevant. This article provides a summary of current data on the structure and functions of neutrophils (NF) in physiological processes. Particular attention is paid to the participation of neutrophils in the damage and formation of vascular endothelial dysfunction. Discusses several mechanisms of involvement of neutrophils in atherogenesis: the production of reactive oxygen species, which cause direct endothelial damage; the synthesis of cytokines that trigger the migration of leukocytes in inflammation; the formation of protein complexes with cholesterol, contributing to their deposition in the vessels, and neutrophil traps, triggering destructive-alterative reactions.